Analysis of the Influence of Work Culture on Employee Performance in the Islamic Guidance Section of the Ministry of Religious Affairs Office of Langkat Regency - Azhar Azhar; Ikhsan Ferdiansyah; Rahmad Panusunan Siregar; Salawati Salawati; Mhd. Sopian (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to analyze the influence of work culture, loyalty, and job satisfaction on employee performance at the Islamic Community Guidance Section of the Ministry of Religious Affairs Office, Langkat Regency. The research method used a quantitative approach with a saturated sample of 35 respondents. Data analysis techniques included validity tests, reliability tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and coefficient of determination. The results showed that partially, work culture had a positive and significant effect on employee performance with a t-count of 3.738 > t-table 1.690 and significance of 0.000. Loyalty also had a positive and significant effect with a t-count of 3.571, as did job satisfaction with a t-count of 3.782. Simultaneously, all three variables had a positive and significant effect on employee performance with an F-count of 7.685 > F-table 2.90 and significance of 0.001. The coefficient of determination showed a contribution of 69.2%, while the rest was influenced by other factors. In conclusion, improving work culture, loyalty, and job satisfaction will enhance employee performance.